2016
DOI: 10.1111/mpp.12395
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal fission is induced during appressorium formation and is required for full virulence of the rice blast fungus

Abstract: Peroxisomes are involved in various metabolic processes and are important for virulence in different pathogenic fungi. How peroxisomes rapidly emerge in the appressorium during fungal infection is poorly understood. Here, we describe a gene, PEF1, which can regulate peroxisome formation in the appressorium by controlling peroxisomal fission, and is required for plant infection in the rice blast fungus Magnaporthe oryzae. Targeted deletion of PEF1 resulted in a reduction in virulence and a delay in penetration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…To explore whether the attenuated virulence in Δ Modnm1 , Δ Momdv1 , and Δ Mofis1 mutants is due to defects in peroxisomal and mitochondrial fission, appressoria from the mutants and wild type strain were treated with oleate and glycerol to induce peroxisomal and mitochondrial fission, respectively [ 32 , 61 63 ]. Globular peroxisomes and mitochondria were markedly increased in deletion mutants as well as in the wild type after treated with 0.1% V/V oleate or 1% V/V glycerol for 10 h, respectively ( S5A–S5D Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore whether the attenuated virulence in Δ Modnm1 , Δ Momdv1 , and Δ Mofis1 mutants is due to defects in peroxisomal and mitochondrial fission, appressoria from the mutants and wild type strain were treated with oleate and glycerol to induce peroxisomal and mitochondrial fission, respectively [ 32 , 61 63 ]. Globular peroxisomes and mitochondria were markedly increased in deletion mutants as well as in the wild type after treated with 0.1% V/V oleate or 1% V/V glycerol for 10 h, respectively ( S5A–S5D Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with recent studies that showed Pex11A, Pex19 and MoPef1 (Mdv1) are required for peroxisomal proliferation and virulence of M . oryzae [ 14 , 28 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression levels of MoGRP1 were examined by quantitative RT-PCR (qRT-PCR). Wildtype samples were prepared from vegetative hyphae, conidia, appressoria, and infected barley leaves (Chen et al 2017). MoGRP1 was widely expressed among these samples, among which the conidia exhibited the highest expression level (Fig.…”
Section: Mogrp1 Is Localized To the Nucleus And Is Constitutively Expmentioning
confidence: 99%
“…There is only one counterpart of Mdv1/Caf4 protein in M. oryzae , named PEF1 [peroxisome fission protein 1] [ 33 ]. This gene may play dual roles of Mdv1 and Caf4, because deletion of PEF1 will lead to evident peroxisomal fission defect during the fission inducing conditions.…”
Section: Life Cycle Of the Peroxisomesmentioning
confidence: 99%